(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Amputation of the lower limb is a serious psycho-emotional trauma, with serious functional, psychological and social consequences for the patient, which affect the duration and quality of life. Unfortunately, as a result of hostilities in Ukraine, the number of amputees is constantly growing. In addition to these problems associated with amputation, a serious and still unresolved issue is the treatment of phantom pain, which is poorly amenable to pharmacological therapy and sometimes makes life unbearable for amputees. The aim of the study was to analyze the effect of mirror motor therapy and phantom motor skills on reducing the intensity of phantom pain in amputated limbs. Materials and Methods. The study used methods of theoretical (generalization of scientific and methodological literature on the subject of the study, analysis of case studies) and practical levels of research (development of methods for conducting mirror and phantom motor research, selection of therapeutic exercises for their implementation, setting time limits for this treatment). Results: 16 patients with lower limb entanglements at the level of the thigh and lower leg - 1.5-2 years ago, with severe and very severe phantom pain - were included in the experimental study. Patients were randomly divided into two groups - control and main. Patients in the control group were treated according to the usual rehabilitation program in this institution - physical therapy exercises, massage, physiotherapy procedures. In addition to the above therapy, the main group was additionally engaged in experimental methods that we proposed to overcome phantom pain – mirror gymnastics and phantom motor skills. All details of the pedagogical experiment were agreed upon with members of the rehabilitation team and patients. The experiment lasted for a month (4 weeks), during which three test measurements of the intensity of phantom pain manifestations in patients were conducted (at the beginning of the experiment, after 2 weeks and after 4 weeks - after the end of the experiment). The intensity of pain manifestations was determined by two scales: a 10-point visual analog pain scale; and an 8-point behavioral pain scale. Results. After 4 weeks of the experiment, according to subjective manifestations (data from visual-analog table 2) the intensity of phantom pain in patients of the main group decreased by 38.9% against 17.5% in the control group (difference 21.4%), and according to objective sensations (table 3), respectively, by 41% against 14.3 (difference 26.8%). Conclusions. Physical, psychological and social adaptation of patients with phantom pain after lower limb amputation is a multifaceted and complex process. Since there are no reliable methods for overcoming phantom pain after amputation, it is necessary to continue researching various aspects of this problem. In our opinion, a promising area for combating phantom pain is the widespread use of various means of physical therapy, primarily neuropsychological, namely, mirror motor therapy and phantom motor skills.